2012
DOI: 10.1002/ijch.201200011
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy–Induced Angiogenic Signaling: Consequences and Solutions to Improve Therapeutic Response

Abstract: Photodynamic therapy (PDT) can be a highly effective treatment for diseases ranging from actinic keratosis to cancer. While use of this therapy shows great promise in preclinical and clinical studies, understanding the molecular consequences of PDT is critical to designing better treatment protocols. A number of publications have documented alteration in angiogenic factors and growth factor receptors following PDT, which could abrogate treatment effect by inducing angiogenesis and re-establishment of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 77 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…An antibody against murine VEGF highly suppressed the release of host VEGF and its addition to the treatment regimen resulted in a more durable treatment response (Fig. 3.6) [79]. These data emphasize the importance of the host cells that compose the tumor microenvironment in dictating the therapy-determining activation of molecular pathways.…”
Section: The Importance Of Combination Therapy To Overcoming Treatmenmentioning
confidence: 79%
See 3 more Smart Citations
“…An antibody against murine VEGF highly suppressed the release of host VEGF and its addition to the treatment regimen resulted in a more durable treatment response (Fig. 3.6) [79]. These data emphasize the importance of the host cells that compose the tumor microenvironment in dictating the therapy-determining activation of molecular pathways.…”
Section: The Importance Of Combination Therapy To Overcoming Treatmenmentioning
confidence: 79%
“…In H460 human tumor xenografts, it was observed that treatment with BPD-PDT led to a nearly two-fold increase in human VEGF levels compared to untreated tumors [79]. Moderate increases in human VEGF have also been observed in the serum of mice bearing human bladder carcinoma cell xenografts following Hypericinmediated PDT [82].…”
Section: Angiogenic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other cancer therapies, PDT can induce increases in VEGF that contribute to tumor recurrence after treatment (1618). Therefore, if erlotinib attenuates PDT-induced increases in VEGF, we might expect these decreases to contribute to the stronger vascular response in tumors pretreated with erlotinib.…”
Section: Resultsmentioning
confidence: 99%